Adsorption of Indigo Carmine Dye and Copper Ion by Kaolin from Bangka Island - Tahya, Candra Yulius; Cornelia, Melanie; Siregar, Tagor M.; Karnelasatri, Karnelasatri (Indonesian Journal of Chemical Research, 2023)
Indigo Carmine (IC) is a synthetic dye that might promote irritations, vomiting, and diarrhea when orally consumed in high concentrations. Copper is a dangerous heavy metal that tends to accumulate in organisms' cells as a pollutant. Hyperproduction of IC and accumulation of copper in water could cause an environmental problem that must be adequately addressed. Kaolin is found abundant on Bangka Island. Based on XRD analysis, Kaolin Island from Bangka Island consists of two important minerals, Kaolinite and Rectorite. Kaolin has chemical and physical properties, which make it useful in several applications, including as an adsorbent. This study aims to evaluate how Kaolin can adsorb copper ion from acid wastewater (pH < 0.5) and determine natural Kaolin's ability to adsorb IC dye from an aqueous solution. Many factors, including mixing time and number of doses of Kaolin, influence Kaolin's ability to absorb IC. The longer the stirring time, the more IC is absorbed. The optimal temperature for IC adsorption is 25˚C. The optimal kaolin dose for IC adsorption is 20% (m/v). Copper concentration after application of Kaolin tends to decrease, with optimal at 25.09% (m/v) dosage for 19.23% copper removal.